PENGARUH MODAL SENDIRI DAN VOLUME USAHA TERHADAP SISA HASIL USAHA - Wardana, Ahmad; Harahap, Nasruddin Khalil; Abidin Harahap, Raja Zainal (Journal Of Sharia Banking, 2024)
The purpose of the problem in this study is to determine the effect of Own Capital, Business Volume on Total Remaining Results of Operations (SHU) in the Mitra Manindo Cooperative, Siabu District, both partially and simultaneously. The discussion of this research relates to the effect of own capital, business volume on the total remaining business results (SHU). Therefore, the approach taken is a theory related to Own Capital, Business Volume to Total Remaining Results of Operations (SHU). number of samples from 2019-2021 (36 Months). Before performing data processing in SPSS Version 2.0, it is first transformed into Ln (Natural Logarithmic) form. The results of the study show the regression equation as follows: SHU = Rp. 8199372,858 + Rp. 0.218 MS – Rp. 0.165 VU. While the value of Adjust R2 ‎(Adjast R Sguare) is 0.432 or equal to (43.2%), which means the Independent Variable (Own Capital, Business Volume) to the dependent variable (Remaining Operating Results) is 43.2%. While the remaining 56.8% is influenced or explained by other factors. And the hypothesis test shows that the tcount for the equity variable is 2.146, the tcount for Business Volume is (-2.155). While ttable is 2.032. So it can be concluded that Own Capital has a positive effect on the Remaining Results of Operations (SHU) while Own Capital, Business Volume has a negative effect on the Remaining Results of Operations (SHU). Simultaneously Fcount was obtained at 9.587 while Ftable was 2.032, it can be concluded that there is an effect of Own Capital, Business Volume on Remaining Business Results (SHU).